Analysis of The Benefits of Collective Labor Agreements (CLA) in Establishing Harmonious Industrial Relations Between Employers, Workers, and The Government - Nurita Singalodra; Suartini Suartini; Anis Rifai (Bina Nusantara University, 2025)
Collective Labor Agreements (CLA) are a crucial instrument for fostering harmonious industrial relations between employers, workers, and the government. CLAs provide legal certainty, ensure fair management of rights and obligations, and support the creation of a conducive working environment. This study aims to identify the benefits gained by each party employers, workers, and the government through the implementation of CLAs. Using a normative research method, the study analyzes applicable labor regulations and examines the role of CLAs in reducing potential conflicts, increasing productivity, and enhancing cost efficiency. The findings reveal that CLAs offer numerous benefits, including conflict reduction, productivity improvement, more efficient cost management, and the development of a positive image for both companies and the government. The study also highlights the importance of social dialogue in the CLA drafting process and the need for regular evaluation of its implementation. In conclusion, CLAs are a strategic tool for establishing stable, equitable, and sustainable industrial relations. Therefore, it is essential for all parties to strengthen the implementation and oversight of CLAs to ensure the creation of harmonious and productive working relationships.